2013
DOI: 10.3892/ol.2013.1639
|View full text |Cite
|
Sign up to set email alerts
|

99mTcO4− scintigraphic detection of follicular thyroid cancer and multiple metastatic lesions: A case report

Abstract: 99mTcO4− thyroid imaging is often used to detect thyroid diseases that are confined to the neck. However, this examination is not frequently used to detect metastatic lesions of thyroid cancer in the whole body, while 131I imaging is often used to detect the metastases of differentiated thyroid cancers. The present study performed 99mTcO4− thyroid imaging for a 69-year-old patient with a thyroid nodule and incidentally identified a lesion with abnormally increased 99mTcO4− uptake in the chest of the patient. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…10 Wang et al reported a previous case of bone metastases in a preoperative whole body pertechnetate scan in a patient with palpable swelling of the second rib. 11 Another case of multiple bone metastases from a thyroid insular carcinoma was described by Kiratli et al 12 Our case outlines that even without clinical suspicion, extrathyroidal tumor uptake may occur and require physician's attention when reporting this routine examination.…”
Section: Figurementioning
confidence: 62%
“…10 Wang et al reported a previous case of bone metastases in a preoperative whole body pertechnetate scan in a patient with palpable swelling of the second rib. 11 Another case of multiple bone metastases from a thyroid insular carcinoma was described by Kiratli et al 12 Our case outlines that even without clinical suspicion, extrathyroidal tumor uptake may occur and require physician's attention when reporting this routine examination.…”
Section: Figurementioning
confidence: 62%
“…Most studies of 99m Tc-pertechnetate scans in patients with DTC mainly focused on the diagnostic efficiency of thyroid remnant or predicted value of lowto intermediate-risk DTC's therapy response to RAI therapy [7][8][9]. In postoperative 99m Tc-pertechnetate scan, 99m Tcpertechnetate avidity of DTC metastatic lesions is a rare phenomenon, only described by case reports [10][11][12][13][14][15], in which the 99m Tc-pertechnetate-avid metastatic foci were detected serendipitously. Some literature described the clinical characteristics of 99m Tc-pertechnetate-avid metastatic foci in DTC, including distant metastasis like lung and bone [16][17][18].…”
Section: Introductionmentioning
confidence: 99%